Pre-imaginal development of Aedes aegypti in brackish and fresh water urban domestic wells in Sri Lanka - Surendran, S.N.; Jude, P.J.; Thabothiny, V.; Raveendran, S.; Ramasamy, R. (Journal of Vector Ecology, 2012)
There is a long and widely held view that Aedes aegypti (Linnaeus) and Ae. albopictus Skuse (Diptera: Culicidae), the principal mosquito vectors of arboviruses causing yellow fever, dengue, and chikungunya, oviposit and undergo pre-imaginal development only in freshwater collections near human habitations (Barraud 1934, Weaver and Reisen 2010, Walter Reed Biosytematics Unit 2012, World Health Organization 2009). Larval source reduction efforts worldwide, therefore, focus on freshwater habitats of the two vectors. However, Ae. aegypti and the closely related arboviral vector Ae. albopictus were recently shown to also undergo pre-imaginal development in brackish water of up to 15 ppt salt (water with <0.5 ppt or parts per thousand salt is fresh, 0.5–30 ppt salt brackish, and >30 ppt salt saline) in discarded food and beverage containers, as well as abandoned wells and boats, along the coast of the Batticaloa and Jaffna districts in tropical Sri Lanka (Ramasamy et al. 2011). Dengue is endemic to Sri Lanka with 28,473 cases and 185 deaths in 2011. There were 400 dengue cases with four deaths and 1,693 cases with 11 deaths, respectively, in 2011 in the Jaffna and Batticaloa districts of the country. The Jaffna district also experienced an epidemic of chikungunya in 2006-2007 (Surendran et al. 2007). Dengue is of global health concern because of its increasing incidence and spread, associated mortality and morbidity, and the lack of a specific drug or vaccine (World Health Organization 2009). Furthermore, Ae. albopictus has adapted to temperate zones to transmit chikungunya and dengue in Europe (Cavrini et al. 2009, Rezza et al. 2007, La Ruche et al. 2010). Climate change can increase the future global incidence and spread of dengue and other arboviral diseases transmitted by Ae. aegypti and Ae. albopictus (Hales et al. 2002, Ramasamy and Surendran 2011, 2012, Reiter 2001,Weaver and Reisen 2010).